Neomycin affects cardiovascular and hematopoietic system via the PI3K/Akt pathway in zebrafish larvae - Yuan Lin; Qiuping Zhang; Lu Chen; Yingying Liu; Xiaoxi Lin; Xiaoyan Peng; Hua Cao; Yuqing Lei; Xinrui Wang (Ecotoxicology and Environmental Safety)
Neomycin, a widely used aminoglycoside antibiotic, poses potential risks to organism and the environment that remain incompletely evaluated. This study systematically evaluates its toxic effects on zebrafish embryos across physiological, cellular, molecular, and behavioral dimensions. At the physiological level, neomycin exposure induces severe developmental abnormalities, including yolk sac edema, reduced body length, and craniofacial malformations. Developmental disorders of the cardiovascular and hematopoietic systems are confirmed in exposed larvae. In addition, zebrafish larvae exposed to neomycin exhibit significant locomotor deficits, including reduced swimming speed, distance traveled, and impaired responsiveness to light-dark stimulation, indicating reduced activity. Mechanically, neomycin triggers oxidative stress through a dose-dependent elevation of reactive oxygen species (ROS) levels and induces cellular apoptosis through the PI3K/Akt signaling pathway. Collectively, our findings demonstrate that neomycin exerts toxic effects on zebrafish embryonic development, highlighting concerns regarding neomycin exposure risks during early pregnancy and providing critical insights into its potential environmental hazards.